An inward and outward natural gas hydrates growth shell model considering intrinsic kinetics, mass and heat transfer - Shi, Bo-Hui; Gong, Jing; Sun, Chang-Yu; Zhao, Jian-Kui; Ding, Yao; Chen, Guang-Jin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2011)
► The natural gas hydrates formation and growth were studied in the flow loop at three water cuts. ► The gas consumption value increased with increment of water cut. ► The total water conversion rates depended on water cut, amount of dissolved gas and surface/volume ratio of particles. ► An inward and outward natural gas hydrates growth shell model was proposed, considered intrinsic kinetics, mass and heat transfer. ► The simulated results fitted the experimental data well. The natural gas hydrates formation and growth at 2 MPa and 277.15 K were studied at different water cuts for water-in-condensate oil emulsions in the flow loop unit. The variations of gas consumption with time at different water cuts were obtained. The experimental results showed that the gas consumption value increased with the rise of water cut. The total water conversion rates not only depended on the water cuts, but also related to several other factors, two of which were the amount of the dissolved gas and the surface/volume ratio of the particles. No more natural gas transformed into hydrates after 3 h, which was likely caused by intrinsic kinetics, mass transfer and heat transfer limitations. An inward and outward natural gas hydrates growth shell model was proposed considering all the three limitations to simulate the gas and water consumptions to form natural gas hydrates.